Development of Legislation on the Protection of Human Rights in the Field of Occupational Safety and Health - Natalia Opolska; Liudmyla Kupina; Anna Politova; , Olena Fatkhutdinova; Oleh Morozov (NUSANTARA: Journal Of Law Studies, 2026)
This study examines the development of legislation on the protection of human rights in the field of occupational safety and health (OSH) through a comprehensive comparative legal analysis, with particular emphasis on the adaptation of Ukrainian law to international and European standards. The research aims to identify the conceptual evolution of OSH regulation, assess the degree of compliance of national legislation with contemporary human rights requirements, and determine priority areas for further legal reform. The methodological framework combines general scientific methods with special legal approaches, including comparative-legal, formal-dogmatic, systemic-structural, and statistical analysis, enabling a multidimensional evaluation of normative content, institutional mechanisms, and law enforcement practices. The study analyzes key international instruments, particularly the conventions and recommendations of the International Labour Organization and the regulatory framework of the European Union, alongside selected European national models. The findings reveal a significant transformation in legal understanding, whereby occupational safety and health are increasingly recognized as integral components of the broader human rights system rather than solely elements of labor regulation. Although Ukrainian legislation formally reflects many European principles, substantial challenges persist in ensuring systematic coherence, preventive orientation, effective enforcement, and sufficient institutional capacity. Statistical data and comparative assessment confirm the necessity of comprehensive modernization focused on strengthening preventive supervision, enhancing compliance mechanisms, and expanding practical guarantees for workers’ rights. The study contributes to legal scholarship by substantiating a rights-based model of OSH regulation and proposing structured directions for legislative improvement in the context of European integration and contemporary socio-economic challenges, thereby enriching comparative labor law discourse and human rights studies.